Portable Solar Powered Outdoor Charging Station With The Application Of Servo Motor In Sunlight Tracking System With Light Detection Relay Sensor - Abigail N. Gonzales, Engr.; B. Muyot, Dr. Norma (Publisher Cv. Inara, 2022)
The use of renewable sources of power has been greatly encouraged since the turn of the century owing to the limited source of fossil fuels. The richest fuel source in the area of renewable energy is solar energy. This experimental-development study focused on the fabrication and testing of a portable solar powered charging station with servomotor and light sensor and testing its acceptability in terms of functionality, aesthetics, durability and safety. This also focused on the determination of the effectiveness of the solar tracking system in the output voltage and current of the prototype. Moreover, efficiency in charging was also tested. Locally available materials were used in constructing the prototype which as equipped with a solar energy harvesting system and sunlight tracking system using Arduino uno to program the sunlight tracking module. Results of the study indicate that the prototype consisted of a harvesting system and a tracking module which enabled the rotation of the solar panels to the angle where solar energy harvest is maximum throughout the day. The Historic Data Chart of the Climate in the Philippines for the daily sunshine hours was used to determine the exact energy that can be harvested in one sunny day and the factors that will be affecting the On and Off condition of the LDR sensor for the lights. Results also suggest that the prototype is highly acceptable with a rating of very good in all the indicators of functionality, aesthetics, durability and safety. Further, there was a 7.62% and 33.39% increase in the voltage and ampere after installing the sunlight tracking system. Furthermore, it was found that the maximum number of gadgets that can be charged by the solar portable charging station is three laptops with 45 watts poer input in three hours and nine mobile phones with 5 watts power input in two hours or a combined full charge capacity of 575 watt-hours.